(untitled) (Medico Legal Update, 2020)
The aim of this study to determine the potential of Coffea canephora by using chlorogenic acid (CGA) compound associated with macrophages polarization in tuberculosis condition. Exploration of compound by using the Knapsack database and Dr. Duke. Analysis of CGA by using a PASS server with the results ranged score 0-1 probability to be active score. Molecular binding docking receptor and ligand were used Autodock PyrXv9.5 and interactions between molecules using CLUSPRO 2.2. Potential activities of CGA compounds was 3,5-dicaffeoylquinic acid, feruloylquinic acid, and p-coumaroylquinic acid with Pa value close to 1, this indicates that the accuracy of prediction of antioxidant activity was quite high. The results of docking through the attachment pathway of several amino acids showed the potential for side methylation activity ‘which is able to reduced DNMT1 activity thereby suppressing the anti-inflammatory process. Protein interactions based on affinity values were higher among DNMT1 and STAT1 bonds compared to STAT6. The results of the study concluded that the active compound in Coffea canephora was involved in the function of the immune system and it related to the inflammatory process. It is triggers the delivery of antimicrobial cytokine signals and increased antioxidant, it is very necessary in healing tuberculosis disease process.